Separation of dissolved oil from aqueous solution by sorption onto acetylated lignocellulosic biomass - equilibrium, kinetics and mechanism studies - Cheu, S. C. (Elsevier Ltd, 2016)
The potential use of lignocellulosic biomass as oil sorbents was demonstrated through acetylation of mercerized pineapple leaves (M-PAL) using acetic anhydride with catalysts (N-bromosuccinimide and pyridine) in order to enhance its surface hydrophobicity and thus oil sorption capacity for treatment of dissolved oil contaminated wastewaters. The raw and acetylated PAL sorbents, before and after oil sorption, were characterized by a scanning electron microscope (SEM), transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS). The oil sorption experiment was evaluated in batch sorption mode using dissolved o/w solution prepared by mixing crude oil and double-distilled water. It was found that the M-NBS-PAL sorbent yielded better oil sorption performance than R-PAL sorbent due to the replacement of hydroxyl group which has more hydrophobic acetyl group on the PAL surfaces, with strong affinity towards oil. The batch equilibrium data were fitted well by Langmuir isotherm model with the maximum sorption capacity (qm) of 37.45 and 90.91 mg/g for the R-PAL and M-NBS-PAL sorbents, respectively. The oil sorption process was thermodynamically feasible and exothermic, while the nature of interaction could be described via the physisorption mechanism. The kinetic sorption data were found to be fitted well into the pseudo-second order kinetic model. The sorption-desorption cycle was repeated four times whereby isopropanol was used as a desorbing agent and the results were comparable with freshly prepared sorbent. Finally, the present findings indicate that the lignocellulosic biomass could be a potential alternative as sorbent precursors for oil removal from oil contaminated wastewaters.